Sediment distribution and provenance on the continental shelf off the Mekong River, SE Vietnam: Insights from heavy mineral analysis. (1st July 2020) - Jagodziński, Robert; Sternal, Beata; Stattegger, Karl; Szczuciński, Witold
Graphical abstract: Highlights: Micaceous, limonites and opaque heavy minerals are useful diagnostic features. Lim, Lim-Mi-Chl, Opq/Lim-Chl-Tur, Opq-Tur-(Ep-Zr) and Opq-Amp-(Ep) heavy minerals provinces distinguished on the shelf. Mineral groups: Lim-Chl, Amp-Ep, and Opq-Tur-Zr are attributed to specific source areas and dominant transport paths. Dominant sediment transport from the Mekong River over the continental shelf is southwestward. Vast mixing zone of different modern and relict sediments is east of the Mekong River mouth. Abstract: The continental shelf off southern Vietnam is relatively well studied regarding the dominant transport paths of bulk and fine-grained sediments discharged by the Mekong River. Thus, this region is particularly suitable for testing the applicability of heavy mineral analysis in determining the extent and origin of the sandy fraction of continental shelf deposits supplied mainly by a large river and their distribution over the adjacent extensive shelf. The fine sand fraction of 105 sediment samples from the Mekong River Delta and neighbouring continental shelf is investigated, applying two approaches: i) considering only the transparent non-micaceous mineral assemblage and ii) considering all the identified heavy minerals. The geological complexity of the source areas and local dominance of micaceous and non-transparent heavy minerals require the inclusion of all heavy mineral components when interpreting sediment provenance and dominant transport paths. The most diagnostic heavy minerals, amphibole, chlorite, epidote, limonite, opaques, tourmaline and zircon, are used for this purpose. The investigated continental shelf can be divided into two main regions characterised by various heavy mineral assemblages, namely, SW and NE off the Mekong River Delta. The south-western region is dominated by chlorite and limonite, indicating prevailing southward sediment transport from the Mekong River, whereas the north-eastern region is characterised by amphibole, epidote, opaques, tourmaline and zircon, indicating various sources from SE Vietnam and relict sediments partly covering the continental shelf. Between the two main regions, a large mixing zone is found where sediments from all sources are present, including Mekong River sediments transported eastward.